Campylobacter Jejuni and Thrombotic Thrombocytopenic Purpura - Roman Jaeschke; E Jan Irvine; Jane Moore; John Kelton (Canadian Journal of Gastroenterology)
Gastrointestinal bacterial infections could be associated with multisystem complication due to the thrombotic phenomena. This paper reports the association of Campylobacter jejuni infection and thrombotic thrombocytopenic purpura, and describes a new test for diagnosing thrombocytopenic purpura.